1989
DOI: 10.3109/00016358909004795
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of human saliva

Abstract: Samples of mixed saliva and of parotid and sublingual/submandibular saliva fractions from four donors were subjected to instantaneous solidification in liquid nitrogen followed by sectioning in a microtome/cryostat. The sections were stained with hematoxylin-eosin, periodic acid-Schiff, Alcian blue, Oil-red-O, or Sudan Black B and then examined at the light-microscopic level. In all the sectioned samples several previously never described features were observed, the most pronounced of which were a loose overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Different authors described the presence of globular structures lying within a network structure [29][30][31]. These globular structures, so-called salivary micelles, have been identified in both PAR and whole saliva [32].…”
Section: Salivamentioning
confidence: 98%
“…Different authors described the presence of globular structures lying within a network structure [29][30][31]. These globular structures, so-called salivary micelles, have been identified in both PAR and whole saliva [32].…”
Section: Salivamentioning
confidence: 98%
“…The methods used in this study have already been shown to be valid and accurate by recent morphologic examinations of sections of frozen mixed saliva (Glantz et al, 1989a(Glantz et al, ,b,c, 1991. Again the results of this study showed the method to be useful and to provide material for evaluation of internal salivary structures.…”
Section: Discussionmentioning
confidence: 91%
“…Glantz et al (1988Glantz et al ( , 1989a recently demonstrated the preservation of intrinsic saliva structures by instantaneous immersion of saliva samples into flasks of liquid nitrogen (-185-8°C). After flash freezing and retrieval from the nitrogen, solid pieces of saliva are handled in the same way as any other frozen piece of tissue, i.e.…”
Section: Introductionmentioning
confidence: 99%